Republic of Madagascar : Request for Disbursement under the Rapid Credit Facility-Press Release and Staff Report; and Statement by the Executive Director for the Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Republic of Madagascar's Request for Disbursement Under the Rapid Credit Facility (RCF). The coronavirus disease 2019 pandemic is having a severe impact on Madagascar's economy. Due to dramatic declines in tourism and disruptions to manufacturing and extractive industry exports, as well as transport, communications, and services, real gross domestic product growth is likely to decline sharply. The fiscal situation is also deteriorating rapidly with additional health and social spending outlays and a significant shortfall in tax revenue. Fund support under the RCF is expected to help the authorities meet the urgent fiscal and external financing needs to mitigate the impact of the pandemic. The authorities are taking immediate measures to address the human and economic impact of the pandemic, while preserving macroeconomic stability. These include increases in health spending, help to the most vulnerable, support to the private sector, and actions to preserve the stability of the financial sector and maintain the flexible exchange rate regime.